Padeye Strength Analysis of Topside Offloading Platform due to Loadout Using Lifting Method - Yoyok Setyo Hadiwidodo; Handayanu Handayanu; Ilham Kharisma Prayoga (Department of Ocean Engineering, 2024)
Lifting is one method in the loadout process. Lifting is the activity of moving a structure using the help of a crane. The loadout process moves the structure from the yard to the barge. In this study, a lifting analysis was carried out on the topside offloading platform structure. The analysis also considers the center of gravity shift factor, dynamic load factor (DAF), and other safety factors that occur in the structure during the lifting process. Dynamic load factor using Dynamic Amplification Factor. Cog shift during lifting affects the amount of load being lifted. The most significant load received by the lifting point is 872.507 kN at lifting point 3. During the lifting process, no failure was found in the structural members, as evidenced by the maximum UC value of 0.87. The Padeye used is designed according to the DNV OS-H205 criteria. Several checks on the padeye structure were carried out, comparing the stress that occurred with the allowable stress on several stress reviews, such as tensile stress, shear stress, and bending stress. Local analysis was also carried out on the padeye structure to determine the stress on the padeye structure. Local analysis of the padeye structure was conducted using the ANSYS Workbench software. The results of the regional analysis showed the equivalent von-mises of 164.96 MPa in the padeye structure and 140.04 MPa at the joints, with the allowable stress of ASTM A36 steel material of 250 MPa.